VOLARE: Adaptive Web Service Discovery Middleware for Mobile Systems - Papakos, Panagiotis; Rosenblum, David; Mukhija, Arun; Capra, Licia (Electronic Communications of the EASST, 2009)
With the recent advent and widespread use of smart mobile devices, the flexibility and versatility offered by Service Oriented Architecture's (SOA) makes it an ideal approach to use in the rapidly changing mobile environment. However, the mobilesetting presents a set of new challenges that service discovery methods developed for nonmobile environments cannot address. The requirements a mobile client device will havefrom a Web service may change due to changes in the context or the resources of the client device. In a similar manner, a mobile device that acts as a Web service provider willhave different capabilities depending on its status, which may also change dramatically during runtime. This paper introduces VOLARE, a middleware-based solution that will monitor the resources and context of the device, and adapt service requests accordingly. The same method will be used to adapt the Quality of Service (QoS) levels advertised by service providers, to realistically reflect each provider's capabilities at any given moment. This approach will allow for more resource-efficient and accurate service discovery in mobile systems and will enable more reliable provider functionality in mobile devices.